2016
DOI: 10.1016/j.stem.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Coupling with Cardiac Muscle Promotes Maturation of hPSC-Derived Sympathetic Neurons

Abstract: Summary Neurons derived from human pluripotent stem cells (hPSCs) are powerful tools for studying human neural development and diseases. Robust functional coupling of hPSC-derived neurons with target tissues in vitro is essential for modeling intercellular physiology in a dish and to further translational studies, but has proven difficult to achieve. Here, we derive sympathetic neurons from hPSCs and show they can form physical and functional connections with cardiac muscle cells. Using multiple hPSC reporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
137
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(149 citation statements)
references
References 44 publications
12
137
0
Order By: Relevance
“…8d), and we did not detect noradrenaline release by HPLC ( data not shown ), suggesting an immature AN-like phenotype. A recent study showed that only upon co-culture with mouse cardiomyocytes, HES-derived sympathetic neurons express such late markers, further supporting our immaturity hypothesis 26 . When we applied the AN-like protocol to FD-PSC lines, we found that cells from severe FD patients could not effectively generate the CD49D + NC, in contrast to control and mild FD cells (Fig.…”
Section: Resultssupporting
confidence: 78%
“…8d), and we did not detect noradrenaline release by HPLC ( data not shown ), suggesting an immature AN-like phenotype. A recent study showed that only upon co-culture with mouse cardiomyocytes, HES-derived sympathetic neurons express such late markers, further supporting our immaturity hypothesis 26 . When we applied the AN-like protocol to FD-PSC lines, we found that cells from severe FD patients could not effectively generate the CD49D + NC, in contrast to control and mild FD cells (Fig.…”
Section: Resultssupporting
confidence: 78%
“…More recently, we have investigated the biophysics of neuro‐cardiac signalling, aiming to address whether the neuronal effects on the heart were the result, in accordance with the archetypal description of cardiac physiology, of the unabridged propagation of sympathetic neurotransmitters throughout the myocardium, or whether neuro‐cardiac communication was confined to specific junctional sites, similar to those involved in skeletal muscle contraction (Hall & Sanes, ; Homan & Meriney, ). This latter hypothesis arose from the results of several previous studies obtained in vitro (Chun & Patterson, ; Shcherbakova et al ., ; Oh et al ., ) and ex vivo (Fukuda et al ., ), suggesting that specific sympathetic synapses may exist in the heart. By applying SN optogenetics, we demonstrated in vivo that neurotransmission underlying the rapid and efficient chronotropic effect of SN activation depended on the local release of NE at the intercellular contact site, with features typical of synaptic transmission (Prando et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…In 2015 [30], experiments demonstrated that having sympathetic neurons present in in-vitro cardiac cultures delays cardiomyocyte cell cycle withdrawal and transiently limits hypertrophy via a β-adrenergic signaling pathway, which suggests that sympathetic innervation can regulate cardiomyocyte numbers during the postnatal period. Developmental changes may occur in neurons as well: Oh et al 2016 reported increased maturation of hiPSC-derived sympathetic neurons in their cardiac neuron co-culture system [31]. Coppen et al have suggested the existence of post-natal changes in connexin expression in the developing fetal heart [32].…”
Section: Discussionmentioning
confidence: 99%